Genetic and microenvironmental intra-tumor heterogeneity impacts colorectal cancer evolution and metastatic development - Sobral, Daniel (2022)
We thank João Neto and remaining Computational Multi-Omics Lab members at UCIBIO for their helpful comments and suggestions. © 2022. The Author(s).